Plato’s Question “Why?”: An Analysis of Resp. 509 b–c through Tim. 29 d–30 a - Ramón Cámara, Begoña (Problemos, 2025)
In Resp. 509 b–c, Plato attributes to the Form of the Good an efficient causality, but he does not explain the matter in detail. This has led some scholars to interpret it in reference to the ‘unwritten doctrines’. The aim of this paper is to link this passage to the cosmological myth narrated in the Timaeus and to make sense of it in the light of Tim. 29 d–30 a, where Plato asks why the world of becoming exists in addition to the world of Ideas, and he gives an allegorical answer by appealing to the goodness of the Demiurge.